Extracorporal Shock Wave Therapy as a Delay Procedure to Improve Viability of Zone 4: An Experimental Study in a Rat TRAM Flap Model. Issue 2 (August 2016) - Nacak, Utku; Calis, Mert; Atilla, Pergin; Cetin, Alp; Aksu, Ali Emre
Abstract : Background: The purpose of this study was to test our hypothesis that preoperative application of radial extracorporeal shock wave therapy (rESWT) as a delay procedure would improve the survival of zone 4 of transverse rectus abdominis musculocutaneous (TRAM) flap and reduce the resulting necrotic area. Methods: Twenty-four Wistar rats were randomized and divided into 3 experimental groups (n = 8 each). Caudally based TRAM flap model, with the right rectus abdominis muscle as the carrier and right inferior epigastric vessels as the vascular pedicle, was used in this study. In group 1 (control), after being raised, the TRAM flap was sutured back to its bed without any further intervention. In group 2, the TRAM flap was raised, and rESWT was administered immediately after the flap was sutured back to its bed. In group 3, rESWT was applied 7 days before the elevation of the flap, as a delay procedure. Seven days after the administration of rESWT, TRAM flap was raised and then sutured back to its bed. Results: At postoperative day 5, the mean percentage of skin flap survival was 61.82 ± 12.22 for group 1, 77.65 ± 4.62 for group 2, and 79.89 ± 5.86 for group 3. Groups 2 and 3 revealed higher survival areas when compared with control group ( P = 0.02). In rESWT applied groups 2 and 3, the increase in capillary density and dilatation of microvessels in the skin flap survival areas were obvious. Histologic analysis revealed significantly higher neovascularization and less inflammation in zone 4 of rESWT applied groups ( P < 0.001 and P = 0.042, respectively). Conclusions: ESWT appears to be a cheap, practical, and promising option for improving the viability of zone 4 of TRAM flap and may also be used as a delay procedure in the clinical setting.